RETRACTION : PREVALENCE OF DEPRESSION IN FIRST-YEAR MEDICAL STUDENTS AT AIRLANGGA UNIVERSITY, INDONESIA - Izzah, Dina Arini; Yitnamurti, Suksmi; Rehatta, Nancy Margarita (Journal of Community Medicine and Public Health Research, 2021)
Depression is a mental disorder with a relatively high prevalence rate in medical students around the world. Medical students are often faced with a variety of pressures ranging from academic to social stress so that the prevalence of depression in medical students tends to be higher than general population. Therefore, this study aimed to find out the prevalence of depression in medical students at Airlangga University. This research was a descriptive cross-sectional study. The sample used was 86 first-year medical students at Airlangga University, Indonesia in the academic year of 2017/2018. The data collection was carried out using Beck Depression Inventory II questionnaires as a measurement instrument. The data was analyzed by descriptive univariate using SPSS 16.0. From 86 samples obtained from first-year students, 37.20% of them experienced mental conditions that were considered abnormal (mean score of 10.14 ± 7.093), starting from mild mood disturbance (23.26%) to the most severe category, severe depression (1.16%). There was no extreme depression category in this study. Furthermore, mean score of male subjects is 8.57 ± 6.120 while mean score of female subjects is 10.64 ± 7.351. This study revealed that the prevalence of depression in first-year medical students at Airlangga University in the second semester of academic year 2017/2018  is quite high, which is more than one third of the total respondents while the prevalence in female subjects is higher than in male subjects.